EPIDEMIOLOGICAL FEATURES IN CHILDREN WITH BRONCHIAL ASTHMA - Левенець, С.С.; Горобець, Н.М. (World of Medicine and Biology, 2018)
Epidemiological analytic investigations of frequency of factors of high humidity in 125 children aged 1 - 18 years with both intermittent and persistent bronchial asthma combined with atopy or without it have been performed. The following investigations have been prompted by ISAAC findings testifying to the highest prevalence of bronchial asthma in the countries of Oceania which is one of the moistest places on the Earth. The article highlights data about frequency of living near open water, in houses with high humidity and covered with a mold walls, dependence on exacerbations of the disease from moist weather and moist seasons (autumn and spring) among asthmatic children. It has been found out that children with persistent bronchial asthma are more dependent on moist season, more frequently live in places with high humidity such as moist houses and close to open water places (river, lake or pond) rather than patients with intermittent course of the disease. Children with intermittent asthma have more often exacerbations in wet seasons; frequency of attacks corresponds to the same in children with persistent course of the disease. Insignificant amount of them live in places with high humidity. Children with both intermittent and persistent bronchial asthma combined with atopy have been shown higher osmotic bronchial hyperreactivity; they more often live in place with high humidity and have more often exacerbations of the disease related to wet weather and wet seasons rather then nonatopic children. Asthmatic nonatopic patients with different course of the disease have similar frequency of living near open water, seasonal exacerbations and meteorological dependence on wet weather; it is remarkably lower the same in atopic patients. They are the least likely to live in houses with high humidity. Bronchial osmotic hyperreactivity factors in asthmatic children have been analyzed in the study by analyzing life conditions, meteorological dependence on wet weather and exacerbations in seasons with increased humidity (autumn and spring). While analyzing childrens’ life conditions living in the areas close to open ponds (rivers, lakes, ponds and reservoirs), living in houses with high humidity and walls covered with mold testifying to unfavorable ecology of housing have been taken into account. Interviewing has been performed by questioning of 125 atopic and nonatopic children aged from 1 to 18 years sick with intermittent and persistent bronchial asthma. The group of atopic children also included patients with atopic dermatitis. It has been found out that children with persistent bronchial asthma are more often meteorologically dependent on wet weather and are more likely to develop exacerbations in seasons with high humidity (spring and autumn) rather than children with intermittent bronchial asthma. Almost half of children with persistent asthma had been living in places with high humidity: houses with increased humidity, close to open ponds. In children with intermittent bronchial asthma exacerbations of the diseases were more likely to develop in moist seasons corresponding to the same frequency of relapses in persistent course of the diseases. The least amount of children with intermittent asthma were living close to open ponds, houses with high humidity and/or walls covered with mold. Combination of several factors causing bronchial osmotic hyperreactivity in asthmatic children was more common for persistent course rather than for intermittent one. Quantity of children with complicated atopic anamnesis including atopic dermatitis was reliably higher among patients with persistent bronchial asthma rather than among those ones with intermittent one. Analysis of factors in atopic and nonatopic children with persistent and intermittent courses of asthma revealed more remarkable bronchial osmotic hyperreactivity in atopic children revealing the influence of living in places with high humidity, houses with walls covered with mold and exacerbations developing in wet weather and moist seasons. The least number of asthmatic children with concomitant atopy or without it, intermittent course of the disease or persistent one were living in houses with high humidity and walls covered with molds. Factor of living in houses with high humidity and walls covered with molds was of the least influence on bronchial osmotic hyperreactivity in asthmatic nonatopic children with intermittent and persistent courses of the disease.